2008
DOI: 10.1029/2007jc004640
|View full text |Cite
|
Sign up to set email alerts
|

A case study of the tropical Hot Event in November 2006 (HE0611) using a geostationary meteorological satellite and the TAO/TRITON mooring array

Abstract: Qin et al. have found Hot Events (HE), which are short‐term (about 20 days) large‐scale (about 15,000,000 km2) regions with very high Sea Surface Temperatures (SST > 30°C). Following their definition, an HE was identified in the tropical western Pacific in November 2006, which is named HE0611. A case study of HE is conducted by using the advanced satellite products and in‐situ measurements from the TAO/TRITON mooring array. Two parts (HE0611‐East and ‐West) with very high SST connected to form HE0611. SST in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…During HEs, latent heat release is suppressed, which in turn suppresses the surface evaporation process. Moreover, Qin et al (2008) and Kawamura (2009, 2010) found evidence of subsiding air during HEs. Hence, frequent HE occurrence may influence vapor transport through the large-scale circulation.…”
Section: Summary and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…During HEs, latent heat release is suppressed, which in turn suppresses the surface evaporation process. Moreover, Qin et al (2008) and Kawamura (2009, 2010) found evidence of subsiding air during HEs. Hence, frequent HE occurrence may influence vapor transport through the large-scale circulation.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…Over the course of 10 years (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003), they identified 31 HEs distributed in the tropical oceans, with most of the HEs (68 %) detected in the western equatorial Pacific. This and subsequent studies concluded that the HEs occur when there are high levels of solar radiation and low wind speeds, and that HE development involves a high diurnal SST amplitude Qin et al 2007Qin et al , 2008Kawamura 2009, 2010). However, there are still some problems with their detection method.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…With an advent of remote sensing technologies through clouds, newgeneration satellites provide an improved monitoring of the ocean-atmosphere conditions at high resolutions (Wentz et al 2000). Based on satellite-derived daily SST, the large-scale phenomena of very high SST even with a short life cycle of 2-3 weeks can be well detected over the Indo-Pacific warm pool (Qin et al 2007). These high-SST events (here called hot events) have a shorter time scale and but larger area size than the hot spots defined by monthly SST in Waliser (1996).…”
Section: Introductionmentioning
confidence: 98%
“…Statistics of hot spots/events show that their occurrences probably respond to the influence from intraseasonal, seasonal, and interannual variability (Waliser 1996;Qin et al 2007). On the intraseasonal time scale, the evolution of hot spots particularly during TOGA COARE has been linked to the organized convection of the MJO Johnson et al 2001;Duvel and Vialard 2007).…”
Section: Introductionmentioning
confidence: 99%